National Academic Conference – Financial Crime in Poland - Trawiński, Tomasz (Studia Historiae Oeconomicae, 2016)
This is a speech by superintendent Tomasz Trawinski, the regional police commander in Poznań, who opened the first of the series of conferences devoted to the history of financial crime in Poland. The present threat of escalating financial crime is not only the concern of the agencies established for fighting this abnormality but also of other institutions which can potentially be of help in fulfilling this task. In this field, the Polish police is open to new forms of cooperation and one of them is the collaboration with academic and scientific centres.